2016
DOI: 10.7205/milmed-d-15-00223
|View full text |Cite
|
Sign up to set email alerts
|

Women in Combat: Framing the Issues of Health and Health Research for America's Servicewomen

Abstract: The Department of Defense should continue to explore and address policy, research, and practice related to the complex ongoing needs of military females in combat roles, and ensures sufficient staffing, resources and support from senior military leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…With the increasing participation and higher levels of performance of women in endurance athletics (30) and with higher expectations of women serving in active military service (41), there have been concerns regarding the susceptibility of women to exertional heat illness (EHI) and exertional heat stroke (EHS) (19,29,31). In military medicine, heat stroke is a subset of heat illness and in most cases it involves exertion in the heat.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing participation and higher levels of performance of women in endurance athletics (30) and with higher expectations of women serving in active military service (41), there have been concerns regarding the susceptibility of women to exertional heat illness (EHI) and exertional heat stroke (EHS) (19,29,31). In military medicine, heat stroke is a subset of heat illness and in most cases it involves exertion in the heat.…”
Section: Introductionmentioning
confidence: 99%
“…15 Shaw and colleagues' study of Veteran births in California reconfirmed this growth, and notably found that by 2012 the fraction of pregnant Veterans relying on VA for maternity benefits had grown markedly to 14%, nearly equaling those relying on Medicaid (15%) for maternity benefits. 13 A smaller analysis, by Katon et al, which relied on 2008-2009 National Survey of Women Veterans, found a slightly higher self-reported fraction of use of VA maternity benefits: 29% of 334 VA-eligible Although women have historically been excluded from serving in direct combat positions, even before recent changes in policy, 23,24 they have frequently worked in supportive roles that put them in the line of direct fire which may cause considerable stress. 25 Women, like their male colleagues, may return from conflicts with mental health problems.…”
Section: Who Takes Care Of Pregnant Veteransmentioning
confidence: 99%
“…Previous trends in military culture suggested shifts toward a more inclusive and accepting culture (Dunivin, ). Evidence of this change includes reduced restrictions placed on women in combat (fully implemented by 2016; McGraw, Koehlmoos, & Ritchie, ) and the repeal of “don't ask, don't tell” (the military's policy of removing personnel who reveal their sexual orientation to be gay or lesbian, repealed in 2010; Hoover, Tao, & Peters, ). The Trump administration, however, is trying to repeal policies that have advanced the equality of service members, although no legislation has been passed toward those efforts at the time of writing.…”
Section: Creation Of Military Family Leisure Experiencesmentioning
confidence: 99%